1967
DOI: 10.1128/am.15.4.736-737.1967
|View full text |Cite
|
Sign up to set email alerts
|

Use of Membrane Filter Technique in the Microbiological Control for the Brewing Industry

Abstract: A physical method was developed involving serial filtration with membrane filters for separating yeast cells from bacteria. Such a method eliminates the need for antibiotics previously required to permit differential counting of such populations. All yeast cells filtered were successfully retained and cultivated on a 1.2-μ membrane filter by use of a synthetic medium. All bacteria filtered avoided entrapment on a 1.2-μ membrane filter and were successfully retained and cultivated on a 0.22-μ membrane filter wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1970
1970
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…An additional filtration unit was placed in each sampled area for bacterial counting, as a punctual contamination marker. The UFC count was recorded, as by Nobile (1967) and Hernández-López et al (1995), with some modifications. In brief, 22 mm diameter filters with 0.22 mm pores and petri plates with tryptic soy agar (TSA) containing 0.1% of tetrazolium violet were used and incubated for 24-48 h at 35 C. Colony forming units (CFU) were counted and the bacteria that were obtained were analyzed by colonial morphology, Gram staining and biochemical reactions.…”
Section: Bacterial Count In Sampling Areasmentioning
confidence: 99%
“…An additional filtration unit was placed in each sampled area for bacterial counting, as a punctual contamination marker. The UFC count was recorded, as by Nobile (1967) and Hernández-López et al (1995), with some modifications. In brief, 22 mm diameter filters with 0.22 mm pores and petri plates with tryptic soy agar (TSA) containing 0.1% of tetrazolium violet were used and incubated for 24-48 h at 35 C. Colony forming units (CFU) were counted and the bacteria that were obtained were analyzed by colonial morphology, Gram staining and biochemical reactions.…”
Section: Bacterial Count In Sampling Areasmentioning
confidence: 99%
“…On the other hand, other authors have previously reported the effectiveness of serial filtration for separating yeast cells from bacteria in beer, observing that all bacteria filtered avoided entrapment on a 1.2 µm filter and were successfully retained and cultivated on a 0.22 µm filter [21]. More recently, it has been observed that some bacteria and yeast present in a viable but non-cultivable state could pass through a 0.45 µm filter [11]. It is thus feasible that part of the bacteria inoculated in the wines could have entered in that state due to factors such as alcohol or filtration under vacuum [19], ending in the final eluate.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, a bacterial contamination is more unlikely to happen, but it can be still a big issue for wineries. Bacteria proliferation can lead to a series of defects that are not possible to detect from visual inspection of the bottles, mainly due to bacterial metabolism, such as lactic prickle, bitterness, production of volatile phenols, mousiness, production of biogenic ammines, and production of ethyl carbamate, a highly harmful molecule [11,12]. Thus, the choice of a method able to detect and distinguish the contamination from yeasts and bacteria would be of primary importance [13].…”
Section: Introductionmentioning
confidence: 99%